2017
DOI: 10.1021/acs.langmuir.7b01562
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Protects Membranes through a Carpet or Insertion Model Depending on Hydration

Abstract: Curcumin is the main ingredient in turmeric, a common Indian spice. Curcumin shows a broad spectrum of effects, including anti-Alzheimer's and antioxidant properties. An interaction between curcumin and lipid membranes has been speculated as the root cause of this activity, and the molecule is often proposed to protect the bilayer. However, the detailed molecular mechanism of this protection is disputed. There is evidence that curcumin either (a) lies flat on the bilayer and provides a "carpet" for protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 60 publications
4
54
0
Order By: Relevance
“…The results of 2 H and 14 N NMR measurements obtained by Kotenkov et al [12] showed that curcumin is not embedded deep in the lipid bilayer of multilamellar liposomes and interacts mainly with the lipid headgroups. In the carpet model, according to which curcumin lies flat on the lipid headgroups it dehydrates lipid bilayers and decreases fluidity [11]. In the DMPC/cholesterol mixture addition of curcumin amplifies the effect of cholesterol on the ordering of lipid acyl chains [12].…”
Section: Effect Of Curcumin On Lipid Acyl Chain Order and Mobilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The results of 2 H and 14 N NMR measurements obtained by Kotenkov et al [12] showed that curcumin is not embedded deep in the lipid bilayer of multilamellar liposomes and interacts mainly with the lipid headgroups. In the carpet model, according to which curcumin lies flat on the lipid headgroups it dehydrates lipid bilayers and decreases fluidity [11]. In the DMPC/cholesterol mixture addition of curcumin amplifies the effect of cholesterol on the ordering of lipid acyl chains [12].…”
Section: Effect Of Curcumin On Lipid Acyl Chain Order and Mobilitymentioning
confidence: 99%
“…By modulating those properties, curcumin may also make membrane less prone to oxidative stress. Because of that, curcumin's way of action was often compared with that of cholesterol [9][10][11][12]. Similar to cholesterol, curcumin was proposed to be anchored to the lipid bilayer near the phosphate group and to stiffen membranes by inducing segmental ordering of lipids [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strong fluorescence emission of curcumin is an indication of its presence in the lipid membranes, as it is very weakly emissive in water [11,14]. It has also been reported that curcumin inserts into lipid bilayers in a hydrated environment [23]. Further, the same emission maximum in both liposomes and AMLs (503 nm) indicates that nanoparticles do not affect the membranes.…”
Section: Resultsmentioning
confidence: 88%